Um estudo crítico do sexismo : modelos mentais em notícias sobre violência contra a mulher - Souza, Giselle Lopes (2015)
Recently, we observe the attendance of women, victim of aggression, it’s a rising reality and Brazil occupies the 7th position related of cases of violence against the women in a group of 87 countries. Speaking about the capixaba territory, the State of Espirito Santo occupies the first placein a hall country. Between that reality, this research figure itself as an approach that is trying to find out how the discursive structures and strategies work in a reproduction of sexism, in the legitimation of the power and power abuse, in the manipulation strategies, in the social role of Media, thus how the discursive reproduction of dominance and mental control that a group can carry on another group. This research is justify itself in the idea that Media controls what is said and how is said to people, therefore, it assumes the importance to serve the society sharing knowledge and information, by the other hand that information in constructed by manipulation and polarization and privileged mental models. Besides, this study is a result of the researches in Sociocognitive Critical Discourse Analyses that it been developed by van Dijk and it is supported by the Sociocognitive Psychologist Studies. However, the selection process of the corpus is based on the news published in 2013 by the A Gazeta Newspaper that can construct the hypothesis of the violence against womam been based on the male sexist dominance, so that the scenery of violence construct by can also be based in sexists mental models with the proposal of the maintenance male dominance.Talking about the analyses process, we opted for quantified methodology to prove out the high number of cases involving domestic violence against woman after that we proceed with a qualified- interpretative methodology, oriented by theorycal- analytical character of Sociocognitive Discursive Analyses. The results demonstrate that the sexist ideology is present in the journalistic construction and can directly influence its readers, through mental models favored by the symbolic elite and discursive polarization strategies representing the woman in a minority status and social group that does not part of the ruling elite.